A Conversation about Ohio University and the Presidency, 1975-1994 - Ping, Charles J. (Book collections on Project MUSE., 2013)
When Charles Ping first arrived at Ohio University in 1975, the university was experiencing a decline in student enrollment and confronting serious financial challenges. But rather than focusing on its problems, Ping instead concentrated on Ohio University's potential. During the nineteen years that Ping served as president, he guided Ohio University in scholarship, research, and service while substantially increasing the size of the campus through the acquisition of The Ridges. "What attracted me was, essentially, the richness of the campus in people and programs," said Ping.